Shelf Life Prediction of Chocomix Instant Chocolate Beverage Powder Using Accelerated Shelf Life Testing (ASLT) based on Critical Moisture Content Approach - Rifa Nurhayati; Rosi Pratiwi; Baskara Katri Anandito; Ervika Rahayu Novita; Mukhammad Angwar (Reaktor, 2018)
Chocomix chocolate beverage powder is one of the increased value-added cocoa products by Griya Cokelat Nglanggeran. The aimed of this study to estimate the shelf life using Accelerated Shelf Life Testing (ASLT) based on critical moisture content. Results showed that critical moisture content of Chocomix was 4.01 % (db). Moisture sorption isotherm (MSI) curve of Chocomix at 28oC was type II isothermic sigmoidal with 2 curves at the ranged of water activity between 0.24 and 0.68; and the equation was  y = 86.584X3 – 91.893X2 + 28.818X – 0.470. The calculation showed that estimated shelf life of Chocomix stored in 51.89 µm thick package at 28oC was 16.4 months.Keywords: chocolate powder, critical moisture content, moisture sorption isotherm, shelf life